The Effect of L-Dopa/Carbidopa Intestinal Gel in Parkinson Disease Assessed Using Neurophysiologic Techniques. Issue 6 (November 2016) - Bologna, Matteo; Latorre, Anna; Di Biasio, Francesca; Conte, Antonella; Belvisi, Daniele; Modugno, Nicola; Suppa, Antonio; Berardelli, Alfredo; Fabbrini, Giovanni
Abstract : Background: By providing a stable and smooth L-dopa plasmatic level, L-dopa/carbidopa intestinal gel reproduces the physiological continuous dopaminergic receptor stimulation in patients with Parkinson disease (PD), and it therefore represents a suitable tool to investigate the role of the altered dopaminergic neurotransmission in the pathophysiology of motor and sensory abnormalities in this condition. Methods: We studied 11 patients with advanced PD being treated with L-Dopa/carbidopa intestinal gel (LCIG) and 11 age-matched healthy subjects. Bradykinesia was measured by kinematic recording of repetitive finger movements (finger tapping), whereas sensory abnormalities were evaluated using the somatosensory tactile discrimination threshold. All the patients were studied off and on medication, in 2 different experimental sessions. Results: Parkinson disease patients were very slow and hypokinetic during finger tapping, with no progressive reduction in amplitude or speed being observed during movement repetition. Somatosensory temporal discrimination threshold values were higher in PD patients than in healthy subjects. The neurophysiologic assessment of the effects of LCIG in advanced PD patients demonstrates an improvement, although not normalization, of motor and sensory abnormalities. Conclusions: The study provides an objective evaluation of the effects of LCIG on motor and sensory abnormalities in PD. The results suggest that besides dopaminergic mechanisms motor and sensory abnormalities in PD reflect a varying combination of pathophysiologic mechanisms.